EFEKTIFITAS PENDIDIKAN KESEHATAN BERDASARKAN HEALTH BELIEF MODEL TERHADAP PENGETAHUAN TENTANG PENCEGAHAN KOMPLIKASI TB PARU PADA PASIEN DM - Sarma " Laurenti; Yessi " Hasneli N; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstrakDiabetes Mellitus (DM) is a collection of symptoms in a person as a result of high blood glucose levels because the body is not able to control blood glucose in the bloodstream. One of the complications that can occur in patients with diabetes mellitus is a disease Tuberculosis (pulmonary TB) is a respiratory disease caused by mycobacterium tuberculosis that proliferate in the body where there is a lot of blood flow and oxygen. This aims of this study was to know the effect of health education on health by the Health Belief Model on knowledge about the prevention of complications of pulmonary TB in patients with DM. Design of this study was quasy experiment with non-equivalent control group design. Sample of this research were 50 respondents wich divided to 25 respondents as an experimental group 25 respondents as a control group based on inclusion criteria using total sampling technique. Experimental group was given health education based on health belief model within 30 minutes. Measuring instrument used was a questionnaire on knowledge about pulmonary tuberculosis patients with a complication of DM. Univariate analysis and bivariate analysis was measured by dependent Wilcoxon test and independent Mann Wihney t-test. Bivariate analysis showed knowledge p value before and after 0,000 < alpha (0.05) which means that health education based on health belief model was effective for knowledge about the prevention of complications of pulmonary tuberculosis in patients with diabetes mellitus. This reasearch was recommended can be applied health education as one of the media for health promotion.Keywords: Education, Health Belief Model, Pulmonary TB, DM, knowledge